A Comparative Investigation of Regulatory Reform in the Ontario For-hire Trucking Industry - Woudsma, Gerald Clarence (My University, 1994)
This thesis examines the reform of economic regulation as it applies to the for-hire trucking industry in Ontario through a comparative analysis of industry structure and performance before and after the introduction of the Truck Transportation Act (Dec. 15, 1988). The analysis employs intra-provincial shipment level data obtained from Statistics Canada as well as aggregate indicators of industry structure (firm size and numbers) and finances (costs).
With respect to industry structure, the findings suggest that the Ontario for-hire industry may have become more concentrated following reform. However, it is difficult to identify specific industry segments with the data employed. Financial data suggests that while Ontario firms spent more on brokers and rental equipment following reform, their expenditure on taxes and licenses did not change.
With respect to industry performance, there is no apparent widespread decline in average rate levels although certain industry segments do exhibit significant rate declines in the years following reform. This is particularly evident in the truckload segment. The rates for service involving small, less accessible communities do not appear to be affected by regulatory reform. Introducing more sensitive measures into the revenue model to capture the: influence of community size (market conditions) has not provided further insight into this question. Price-discrimination based on commodity type is similarly not affected by reform.
In general, the findings in this thesis suggest that in the case of Ontario, the reform of trucking regulation has not had a substantial impact on the for-hire trucking industry as a whole. This result contradicts the predictions of both the proponents and opponents of regulatory reform.
Keywords: Geography; Geography